Identification of chemical components in Pericarpium Citri Reticulatae by HPLC-MS/MS. Issue 1 (March 2021) - Liu, Ming-Shi; Geng, Lu-Lu; Meng, Fan-Xin; Qin, Shu-Zhi; Wu, Li-Yan; Sun, Hao-Yang
Abstract: In this paper, a novel approach using HPLC-MS/MS (high performance liquid chromatography-tandem mass spectrometry) was established for the identification of Pericarpium Citri Reticulatae (PCR). The identities of the components were researched by comparing the mass spectra and retention times with those of reference compounds and mass fragments with those of the known compounds published in literature. Based on the proposed strategy, ten constituents were identified. The established HPLC-MS/MS method could identify the major constituents in PCR with high efficiency and sensitivity. The new method would be suitable for the chemical identification of main components from Pericarpium Citri Reticulatae.